Light Hygiene for Circadian Health: A Molecular Perspective - Denis Gubin; Oliver Stefani; Germaine Cornelissen (Frontiers in Bioscience-Landmark)
In discussing the interplay between light exposure/blue light exposure (LE/BLE) and circadian health, we emphasize the role of light hygiene and its effects on maintaining sleep, mood, and metabolic health, among other physiological processes. We define compromised circadian light hygiene as low dynamic range and/or irregular 24-hour patterns of LE. Poor light hygiene interferes with circadian entrainment and weakens circadian robustness alignment, thereby increasing health hazards. We provide an overview of the complex molecular pathways underlying light perception and downstream signaling. Given that genetic polymorphisms influence key elements within these light signaling pathways, we propose that personalized light hygiene approaches be designed for populations affected by compromised circadian LE or at risk of light-induced circadian disruption.